Disease Activity Indices in Rheumatoid Arthritis: Comparative Performance to Detect Changes in Function, IL-6 Levels, and Radiographic Progression - Rodriguez-García, Sebastián C.; Montes, Nuria; Ivorra-Cortes, José; Triguero-Martinez, Ana; Rodriguez-Rodriguez, Luis; Castrejón, Isabel; Carmona, Loreto; González-Álvaro, Isidoro (Frontiers in Medicine, 2021)
Objective: To compare the capacity of various disease activity indices to evaluate changes in function, IL-6 levels, and radiographic progression in early and established rheumatoid arthritis (RA). Methods: Secondary data analysis of a clinical trial assessing the efficacy of tocilizumab in patients with established RA (ACT-RAY) and a longitudinal prospective register of early arthritis (PEARL). Targeted outcomes were changes in physical function, measured with the health assessment questionnaire (HAQ), IL-6 serum levels, and radiographic progression. The “Hospital Universitario La Princesa Index” (HUPI), DAS28 and SDAI were the disease activity indices compared. Models adjusted for age and sex were fitted for each outcome and index and ranked based on the R2 parameter and the quasi-likelihood under the independence model criterion. Results: Data from 8090 visits (550 patients) from ACT-RAY and 775 visits (534 patients) from PEARL were analyzed. The best performing models for HAQ were the HUPI (R2 = 0.351) and SDAI ones (R2 = 0.329). For serum IL-6 levels, the SDAI (R2 = 0.208) followed by the HUPI model (R2 = 0.205). For radiographic progression in ACT-RAY, the HUPI (R2 = 0.034) and the DAS28 models (R2 = 0.026) performed best whereas the DAS28 (R2 = 0.030) and HUPI models (R2 = 0.023) did so in PEARL. Conclusions: HUPI outperformed other indices identifying changes in HAQ and radiographic progression and performed similarly to SDAI for IL-6 serum levels.